The effects of anesthetic technique and ambient temperature on thermoregulation in lower extremity surgery - Ozer, Ayse B.; Tosun, Fadime; Demirel, Ismail; Unlu, Serap; Bayar, Mustafa K.; Erhan, Omer L. (Springer Japan Kk, 2013)
The purpose of our study was to determine the effects of anesthetic technique and ambient temperature on thermoregulation for patients undergoing lower extremity surgery. Our study included 90 male patients aged 18-60 years in American Society of Anesthesiologists Physical Status groups I or II who were scheduled for lower extremity surgery. Patients were randomly divided into three groups according to anesthetic technique: general anesthesia (GA), epidural anesthesia (EA), and femoral-sciatic block (FS). These groups were divided into subgroups according to room temperature: the temperature for group I was 20-22 A degrees C and that for group II was 23-25 A degrees C. Therefore, we labeled the groups as follows: GA I, GA II, EA I, EA II, FS I, and FS II. Probes for measuring tympanic membrane and peripheral temperature were placed in and on the patients, and mean skin temperature (MST) and mean body temperature (MBT) were assessed. Postoperative shivering scores were recorded. During anesthesia, tympanic temperature and MBT decreased whereas MST increased for all patients. There was no significant difference between tympanic temperatures in either the room temperature or anesthetic method groups. MST was lower in group GA I than in group GA II after 5, 10, 15, 20, 60 and 90 min whereas MBT was significantly lower at the basal level (p < 0.05). MST after 5 min was significantly lower in group GA I than in group FS I (p < 0.05). Shivering score was significantly higher in group GA I (p < 0.05). There were no significant differences in thermoregulation among anesthetic techniques. Room temperature affected thermoregulation in Group GA.
Keywords: Thermoregulation; General anesthesia; Epidural anesthesia; Femoral sciatic block and ambient temperature